Analysis of sport performance by means of a DLT-2D based photogrammetric system - Navarro, E.; Mallo, J.; Cala, A.; Veiga, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to validate and apply a bi-dimensional photogrammetric video system to collective and cyclic sports. Twenty-one football matches were filmed using three video-cameras positioned at the main stand of the stadiums and computerized analysis of the films was performed using DLT (direct lineal transformation) based algorithms. This procedure was used during the FIFA under-17 World Championship Finland 2003 and the FIFA Confederations Cup 2005 to obtain a detailed kinematical analysis of high-standard official`s physical and technical match-performance. In another study, the frequency and amplitude of cycle of 2 subjects swimming 400m at incremental progressive velocities were analysed with the same methodology.